Study of reading habits 1993 - Gästrikland - Weibull, Lennart (University of Gothenburg, 1999)
This survey forms part of a series of local readership studies undertaken within the research program ´Dagspresskollegiet´. The surveys deals with the relation toward dailies and media in general, and toward the local paper in particular. There are questions about the use of media, dailies read, and what kind of news paper content one reads. This survey is mainly a replication of surveys conducted in the same five municipalities in 1986 and 1989.

This survey forms part of a series of local readership studies undertaken within the research program ´Dagspresskollegiet´. The surveys deals with the relation toward dailies and media in general, and toward the local paper in particular. There are questions about the use of media, dailies read, and what kind of news paper content one reads. This survey is mainly a replication of surveys conducted in the same five municipalities in 1986 and 1989.
Läsvanestudien 1993 - Gästrikland
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap